White matter tract strength correlates with therapy outcome in persistent developmental stuttering. Issue 11 (12th April 2022) - Neef, Nicole E.; Korzeczek, Alexandra; Primaßin, Annika; Wolff von Gudenberg, Alexander; Dechent, Peter; Riedel, Christian Heiner; Paulus, Walter; Sommer, Martin
Abstract: Persistent stuttering is a prevalent neurodevelopmental speech disorder, which presents with involuntary speech blocks, sound and syllable repetitions, and sound prolongations. Affected individuals often struggle with negative feelings, elevated anxiety, and low self‐esteem. Neuroimaging studies frequently link persistent stuttering with cortical alterations and dysfunctional cortico‐basal ganglia‐thalamocortical loops; dMRI data also point toward connectivity changes of the superior longitudinal fasciculus (SLF) and the frontal aslant tract (FAT). Both tracts are involved in speech and language functions, and the FAT also supports inhibitory control and conflict monitoring. Whether the two tracts are involved in therapy‐associated improvements and how they relate to therapeutic outcomes is currently unknown. Here, we analyzed dMRI data of 22 patients who participated in a fluency‐shaping program, 18 patients not participating in therapy, and 27 fluent control participants, measured 1 year apart. We used diffusion tractography to segment the SLF and FAT bilaterally and to quantify their microstructural properties before and after a fluency‐shaping program. Participants learned to speak with soft articulation, pitch, and voicing during a 2‐week on‐site boot camp and computer‐assisted biofeedback‐based daily training for 1 year. Therapy had no impact on the microstructural properties of the two tracts. Yet, after therapy, stuttering severity correlated positively with left SLF fractional anisotropy, whereas relief from the social–emotional burden to stutter correlated negatively with right FAT fractional anisotropy. Thus, posttreatment, speech motor performance relates to the left dorsal stream, while the experience of the adverse impact of stuttering relates to the structure recently associated with conflict monitoring and action inhibition. Abstract : Persistent developmental stuttering relates to white matter changes in the superior longitudinal fasciculus (SLF) and the frontal aslant tract (FAT). While both tracts subserve speech and language functions, the FAT additionally conveys inhibitory control and conflict monitoring. Here we show that the efficacy of an intensive computer‐assisted biofeedback‐based fluency‐shaping program with one year of daily training of a new speech technique relates to the pre‐intervention tract composition of both fiber tracts. Moreover, speech motor improvement builds on the left dorsal language stream, while affective improvement builds on the structure recently associated with conflict monitoring and action inhibition. Previous studies relate the neural substrate of stuttering to speech planning, auditory‐to‐motor coupling, motor timing and sequencing, and speech error monitoring. We observed, in addition, a brain‐behavior relationship that links stuttering to action control and affective aspects of the disease thereby emphasizing the need for system‐level approaches in studying and treating this highly prevalent condition.